2012
DOI: 10.1186/1475-9276-11-79
|View full text |Cite
|
Sign up to set email alerts
|

Mutual research capacity strengthening: a qualitative study of two-way partnerships in public health research

Abstract: IntroductionCapacity building has been employed in international health and development sectors to describe the process of ‘experts’ from more resourced countries training people in less resourced countries. Hence the concept has an implicit power imbalance based on ‘expert’ knowledge. In 2011, a health research strengthening workshop was undertaken at Atoifi Adventist Hospital, Solomon Islands to further strengthen research skills of the Hospital and College of Nursing staff and East Kwaio community leaders t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 17 publications
1
61
0
2
Order By: Relevance
“…En este sentido, se han comunicado la utilidad del intercambio de programas formativos Norte-Sur, pero suelen referirse a aportes del Norte hacia el Sur subdesarrollado que precisa ser formado y ayudado. La integración de la mutualidad o asociación entre países durante los procesos de aprendizaje-enseñanza e investigación tienen un gran beneficio mutuo, pudiéndose beneficiar los profesionales e investigadores de los países con más recursos y menos recursos logrando un fortalecimiento de capacidades en ambos 7,27,28 .…”
Section: -Presencia De Actividades Administrativasunclassified
See 1 more Smart Citation
“…En este sentido, se han comunicado la utilidad del intercambio de programas formativos Norte-Sur, pero suelen referirse a aportes del Norte hacia el Sur subdesarrollado que precisa ser formado y ayudado. La integración de la mutualidad o asociación entre países durante los procesos de aprendizaje-enseñanza e investigación tienen un gran beneficio mutuo, pudiéndose beneficiar los profesionales e investigadores de los países con más recursos y menos recursos logrando un fortalecimiento de capacidades en ambos 7,27,28 .…”
Section: -Presencia De Actividades Administrativasunclassified
“…Sin embargo, el "Sur" no sólo recibe ideas, sino que las genera también 5,6 . En esta situación, faltan estudios comparativos del perfil profesional del MdF -organización del trabajo, actividades, competencias y responsabilidades, satisfacción profesional, relación médico-paciente, etc.-en países industrializadas y emergentes, siendo preciso favorecer la investigación y formación como procesos de doble vía, así como la evaluación adecuada de las fortalezas de los sistemas sanitarios de los países en desarrollo y las redes de colaboración entre países en desarrollo y desarrollados [7][8][9] .…”
Section: Introductionunclassified
“…17 Investigators developed an ordinal scale to assess the frequency, intensity and duration of contact between cases and the puppy with the assessment performed by an ACF staff member familiar with the affected staff and residents. The results showed most contact instances were unplanned, involved occasional patting of the puppy and occurred no more than once or twice per week.…”
Section: (3) Contact With the Puppymentioning
confidence: 99%
“…Similar low coverage of clean cord care was seen in Southern Nepal among home deliveries, increasing the risk of umbilical infections by 29% (due to topical applications) and 62% (due to other unclean practices). 17 A randomized controlled trial in Pakistan showed that training TBAs and their integration into the health system to propagate newer safe practices, such as cord care, were effective in reducing neonatal mortality by 30%. 20 We need to consider strategies to better engage the TBAs to increase the adoption of these practices.…”
mentioning
confidence: 99%
“…9 A subsection of eight people from the main group formed a team to investigate HIV. All described HIV as a public health concern.…”
Section: Methodsmentioning
confidence: 99%